Characterization of Triphenylamine and Ferrocenyl Donor‐π‐Donor Vinyl BODIPY Derivatives as Photoacoustic Contrast Agents. (20th April 2021) - Hatamimoslehabadi, Maryam; Frenette, Mathieu; Bag, Seema; Gilligan, Gerald E.; La, Jeffrey; Yelleswarapu, Chandra; Rochford, Jonathan
Abstract: The photophysical and electrochemical properties for a series of BODIPY dyes with incremental 3‐ and 3, 5‐vinyl conjugation, as well as incremental electron‐donating groups (anisole < triphenylamine < ferrocenyl), are presented. Insight into the influence of each vinyl‐conjugated electron‐donating group on both vis‐NIR absorption and fluorescence emission properties is provided. These trends are further corroborated by density functional theory computational analysis. Two of this series containing the 3, 5‐bis(vinyltriphenylamine) and 3, 5‐bis(vinylferrocenyl) substituents exhibit significant absorption cross sections in the biological transparency window justifying further investigation of their photoacoustic emission properties via both optical photoacoustic z‐scan and photoacoustic tomography experiments. Both the 3, 5‐bis(vinyltriphenylamine) and 3, 5‐bis(vinylferrocenyl) substituted BODIPY dyes exhibit quantitative photoacoustic quantum yields. Relative to the commercially available methylene blue and indocyanine green molecular photoacoustic contrast agents, the 3, 5‐bis(vinyltriphenylamine)‐derived BODIPY exhibits the greatest photoacoustic emission and contrast upon excited‐state absorption at 685 nm excitation at a low power laser fluence (<20 mJ cm ‐2 ). Abstract : The photophysical and electrochemical properties for a series of BODIPY dyes with incremental 3‐ and 3, 5‐vinyl conjugation, as well as incremental electron‐donating groups (anisole < triphenylamine < ferrocenyl), are presented. Optoacoustic z‐scan and photoacoustic imaging of the 3, 5‐bis(vinyltriphenylamine) and 3, 5‐bis(vinylferrocenyl)‐substituted BODIPY dyes are reported relative to the commercially available methylene blue and indocyanine green molecular photoacoustic contrast agents.